PRESERVING HERITAGE THROUGH MATHEMATICS: AN ETHNOGRAPHIC EXPLORATION OF GEOMETRY PRINCIPLES IN BATIK CEPLOK SOGAN SOLO MOTIF - Mutiara Hisda Mahmudah; Berliani Ardelia Sukowati; Ismiyati Ismiyati; Naufal Ishartono (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Batik Ceplok Sogan Solo is one of the traditional batik motifs that has a distinctive golden brown color produced from natural dye of soga tree bark (Peltophorum pterocarpum), but it is less known by the younger generation. Therefore, the integration of batik in mathematics learning is one of the strategies to introduce the batik culture. This research aims at mathematical concepts such as geometry, algebra, arithmetic, and statistics in solo ceplok sogan batik motifs. This research uses qualitative ethnography. The subject of this research is the Solo Ceplok Sogan batik motif. Data validity was obtained through source triangulation, while data analysis included reduction, presentation, and conclusion drawing. The exploration process was carried out by answering four main questions, namely “where do I start looking?”, “How do I find it?”, “How do I recognize that it has found something significant?”, and “How do I understand what it is?”. The results show that of the four math concepts, only one, geometry, was found in this batik. Sub-concepts of flat geometry (quadrilateral and circle), and sub-concepts of plane geometry (congruence and straight line segment), as well as sub-concepts of transformation geometry (dilation, reflection, and translation). These findings can be integrated into mathematics learning through the development of ethnomathematics-based assessments oriented towards High Order Thinking Skills.